AB0457 Clinical features of behçet's disease in tunisian people. (23rd January 2014) - Cherif, I.; Sahli, H.; Tekaya, R.; dridi, L.; Saidane, O.; mahmoud, I.; abdelmoula, L.; Zouari, R.
Abstract : Background: Behçet's disease is an inflammatory disorder of unknown aetiology, characterized by recurrent painful oral ulcer and genital ulcer, skin diseases and uveitis. It may involve cardiovascular, gastrointestinal and central nervous system, as well as joints Objectives: To define the epidemiology and clinical features of Behçet's disease, giving special attention to the rheumatic manifestations. Methods: We retrospectively reviewed the medical records of the patients who met the International Study group criteria of Behçet disease and were treated during the last ten years [2002-2012]. Results: Twenty three patients were treated. The mean age at the diagnosis was 41 years (range 20 to 58 years) with a female to male ratio of 1.5. Mean disease duration was about 4, 4 years (range 6 to 14 years). Joint manifestations were present in 22 cases and were inaugural in 18 cases. Patients presented with inflammatory arthralgia (14 cases) and arthritis (8 cases). It was a monoarthritis in 4 cases, oligoarthritis in 3 cases and polyarthritis in one case. The knee and ankles were the joint most commonly affected. Oral Ulcers and genital ulcers were noted in all cases. Skin lesions were seen in 5 cases: including erythema nodosum-like eruption (2 cases) and pseudofoliculitis (3 cases). Ocular involvement was observed in 11 cases: anterior uveitis, posterior uveitis and retinal vasculitis. Deep venous thrombosis was noted in 3 cases and neurological involvement such (convulsion and cognitive impairement) in 2 cases. Biologic inflammatory syndrome was observed in 16 cases. HLA B51 was positive in 4 cases among the 7 tested. Conclusions: This series confirms the heterogeneity of the Behçet disease in Mediterranean countries. Uveitis and joint manifestations were frequent and inaugural in most cases Disclosure of Interest: None Declared